Eurípides, Helena 435-482. Elementos conversacionales, humor y guiños aristofánicos en una tragedia - Labiano Ilundain, Juan Miguel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
This paper deals with a detailed study of conversational idioms in a well-known scene of Euripides’ Helen, their connatural place in the diction of tragedy, their interaction with some humorous elements, the problems it poses, and the consideration of all of these elements in an eclectic way. As conclusion it may be said that humour and complicity with aristophanic Comedy are introduced by Euripides in this case and that he does not alter the essence of tragedy due to his theatrical talent.
Keywords: Euripides; Tragedy; Conversational idioms; Aristophanes; Humour